EFEKTIVITAS PEMBIAYAAN ULTRA MIKRO DALAM RANGKA PEMBERDAYAAN PEREMPUAN MELALUI PNM MEKAAR SYARIAH - Auliya Muharramah (2023)
Abstract. Ultra micro financing is a financing facility program for Ultra Micro Businesses, both in the form of conventional financing and financing based on sharia principles. Micro Enterprises have considerable potential in overcoming the difficulties faced by women and their families. This ultra-micro financing program can increase women's income by empowering them in the economic sector. The purpose of this study was to analyze ultra-micro financing schemes, analyze the effectiveness of ultra-micro financing to PNM Mekaar Syariah customers and analyze the development of women's empowerment at PNM Mekaar Syariah Pondok Kopi Branch through ultra-micro financing. The research method used is a qualitative method with a case study approach. The results of this study are that the ultra-micro financing scheme complies with the DSN MUI Fatwa No 04/DSN-MUI/IV/2000 concerning Murabahah Financing. The effectiveness of the distribution of ultra-micro financing was measured using 4 indicators, namely targets, call for goals, socialization programs and coaching programs that have been running effectively and have had a positive impact on empowering women, especially micro traders in the Milling area.